Landscape of humoral immune responses against SARS-CoV-2 in patients with COVID-19 disease and the value of antibody testing. Issue 4 (April 2021) - Mahalingam, Sundarasamy; Peter, John; Xu, Ziyang; Bordoloi, Devivasha; Ho, Michelle; Kalyanaraman, Vaniambadi S.; Srinivasan, Alagarsamy; Muthumani, Kar
Abstract: A new pandemic is ongoing in several parts of the world. The agent responsible is the newly emerged severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The symptoms associated with this virus are known as the coronavirus disease-2019 (COVID-19). In this review, we summarize the published data on virus specific antibodies in hospitalized patients with COVID-19 disease, patients recovered from the disease and the individuals who are asymptomatic with SARS-CoV-2 infections. The review highlights the following: i) an adjunct role of antibody tests in the diagnosis of COVID-19 in combination with RT-PCR; ii) status of antibodies from COVID-19 convalescent patients to select donors for plasma therapy; iii) the potential confounding effects of other coronaviruses, measles, mumps and rubella in antibody testing due to homology of certain viral genes; and iv) the role of antibody testing for conducting surveillance in populations, incidence estimation, contact tracing and epidemiologic studies. Abstract : Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2); Diagnosis of COVID-19; Antibody tests; RT-PCR.